1990
DOI: 10.1128/aac.34.7.1393
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibilities of Plasmodium falciparum to compounds which inhibit nucleotide metabolism

Abstract: A unique metabolic feature of malaria parasites is their restricted ability to synthesize nucleotides. These parasites are unable to synthesize the purine ring and must therefore obtain preformed purine bases and nucleosides from the host cell, the erythrocyte. On the other hand, pyrimidines must be synthesized de novo because of the inability of the parasites to salvage preformed pyrimidines. Thus, one would anticipate that the blockage of purine salvage or pyrimidine de novo synthesis should adversely affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 49 publications
2
50
0
Order By: Relevance
“…This observation is consistent with the conclusion that the 6 position (19). Previous kinetic analyses of these compounds as inhibitors showed that the K i s (at 0.42 M for thioguanine and 0.55 M for 6-mercaptopurine) were about 1 order of magnitude lower than the reported K i s (at 2.4 M for thioguanine and 3.9 M for 6-mercaptopurine) of the corresponding enzyme from human erythrocytes (14,19). The previous studies of these two compounds permit them to be used as standards for this recombinant screening method.…”
Section: Vol 39 1995 Recombinant Screening For Parasite Hprt Inhibisupporting
confidence: 82%
See 2 more Smart Citations
“…This observation is consistent with the conclusion that the 6 position (19). Previous kinetic analyses of these compounds as inhibitors showed that the K i s (at 0.42 M for thioguanine and 0.55 M for 6-mercaptopurine) were about 1 order of magnitude lower than the reported K i s (at 2.4 M for thioguanine and 3.9 M for 6-mercaptopurine) of the corresponding enzyme from human erythrocytes (14,19). The previous studies of these two compounds permit them to be used as standards for this recombinant screening method.…”
Section: Vol 39 1995 Recombinant Screening For Parasite Hprt Inhibisupporting
confidence: 82%
“…Of seven additional compounds that we would predict to have at least some antimalarial activity (compounds 40, 44, 48, and 51 to 54) on the basis of their effects on the growth of bacteria expressing the recombinant P. falciparum HPRT, four (compounds 40, 48, 53, and 54) were included in the antimalarial screens (16) and were found to inhibit the growth of P. falciparum (in the range of 25 to 36%). Of the remaining three compounds, 6-mercaptopurine (compound 51) and 6-thioguanine (compound 52) were previously tested for their antimalarial activities in a separate study (19) and were reported to have 50% inhibitory doses for P. falciparum of approximately 6.2 and 18 M, respectively. With the exception of untested compound 44, all of the compounds identified by the recombinant screens as inhibiting the malarial HPRT have been shown to inhibit the growth of P. falciparum …”
Section: Vol 39 1995 Recombinant Screening For Parasite Hprt Inhibimentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike humans, leishmania parasites cannot make purines de novo and must therefore obtain purine bases and nucleotides from the host cell and then metabolize these to nucleotides by salvage pathway (16). A similar mechanism occurs in malaria parasites, which have also demonstrated significant sensitivity to 6-MP, 6-TG and other compounds (17).…”
mentioning
confidence: 97%
“…Orotic acid is the only preformed pyrimidine that is utilized by malarial parasites (19). This, in turn, has inspired evaluation of orotic acid analogs as potential antimalarial agents (18,27,(35)(36)(37)(38). 5-Fluoroorotate inhibited the in vitro proliferation of chloroquine-susceptible as well as chloroquine-resistant P. falciparum with a 50% inhibitory concentration of 6 nM (38).…”
mentioning
confidence: 99%